2013
DOI: 10.1210/en.2013-1757
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of SCF-Skp2/Cks1 E3 Ligase Block Estrogen-Induced Growth Stimulation and Degradation of Nuclear p27kip1: Therapeutic Potential for Endometrial Cancer

Abstract: In many human cancers, the tumor suppressor, p27(kip1) (p27), a cyclin-dependent kinase inhibitor critical to cell cycle arrest, undergoes perpetual ubiquitin-mediated proteasomal degradation by the E3 ligase complex SCF-Skp2/Cks1 and/or cytoplasmic mislocalization. Lack of nuclear p27 causes aberrant cell cycle progression, and cytoplasmic p27 mediates cell migration/metastasis. We previously showed that mitogenic 17-β-estradiol (E2) induces degradation of p27 by the E3 ligase Skp1-Cullin1-F-Box- S phase kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…Our results showed that SKP2 expression is significantly higher in patients with invasive breast cancer than in normal breasts. Previous research has suggested that SKP2 mainly degrades CKI p27 in the cell cycle, while high expression of SKP2 in malignant tumors is often accompanied by significantly reduced p27 (Pavlides et al, 2013;Chan et al, 2014). This is in agreement with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that SKP2 expression is significantly higher in patients with invasive breast cancer than in normal breasts. Previous research has suggested that SKP2 mainly degrades CKI p27 in the cell cycle, while high expression of SKP2 in malignant tumors is often accompanied by significantly reduced p27 (Pavlides et al, 2013;Chan et al, 2014). This is in agreement with our results.…”
Section: Discussionsupporting
confidence: 94%
“…With a similar mechanism, SKP2 E3 ligase inhibitors (SKP2E3LIs), which are another group of inhibitors that block the interaction of SKP2 with p27, efficiently hindered the oestrogen-induced stimulation of cell growth and the degradation of nuclear p27 (REF. 155). …”
Section: F-box Proteins As Therapeutic Targetsmentioning
confidence: 99%
“…SR microscopy circumvents the conventional resolution limit of light microscopy by temporally separating emitting fluorophores and computationally fitting the location of each below the diffraction limit. Reconstructing thousands of points in this manner generates an image with a resolution typically an order of magnitude better that that of conventional microscopy (32)(33)(34). In addition to this approach, we used smFRET, a powerful method capable of monitoring the dynamics of individual nucleoprotein complexes in real time (35).…”
mentioning
confidence: 99%